Забезпечення інформаційної безпеки в процесі розробки та імплементації стартап-проєктів - Сергієнко, Олена Андріанівна; Соснов, Ігор Ігорович; Іпполітов, Євгеній Миколайович (The University of Technology in Katowice Press, 2025)
The study focuses on ensuring information security by protecting the intellectual property and confidential data of startups, particularly through encryption methods, the use of legal mechanisms, and secure data storage. Practical aspects of information security are examined, including the implementation of cybersecurity policies, technological solutions for data protection, and improving cyber hygiene among personnel. The study provides a detailed analysis of information security challenges during the scaling phase of a startup, covering IT infrastructure protection, security audits, and incident response planning. Recommendations are proposed to enhance the level of information security in startups.
Ensuring information security in the process of development and implementation of startup projects
Keywords: інформаційна безпека; стартап; стартап-проєкти; бізнес; цифрова трансформація; інноваційні технології